Improved luminosity determination in pp collisions at [Formula: see text] using the ATLAS detector at the LHC - ATLAS Collaboration; Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; et al. (The European physical journal. C, Particles and fields, 2013)
The luminosity calibration for the ATLAS detector at the LHC during pp collisions at [Formula: see text] in 2010 and 2011 is presented. Evaluation of the luminosity scale is performed using several luminosity-sensitive detectors, and comparisons are made of the long-term stability and accuracy of this calibration applied to the pp collisions at [Formula: see text]. A luminosity uncertainty of [Formula: see text] is obtained for the 47 pb-1 of data delivered to ATLAS in 2010, and an uncertainty of [Formula: see text] is obtained for the 5.5 fb-1 delivered in 2011.